(untitled) - Larsen-Freeman, Diane (Oxford, 2000)
The book is a fully revised and updated edition of this popular introduction to language teaching methodology which explores language teaching methods and recent methodological innovations. It provides an excellent overview for the beginning teacher, or for non-ESL teachers who need some background about terminology and methods which is not too technical.
Phương pháp dạy học Tiếng Anh
Keywords: English language; Study and teaching,Foreign speakers